2020
DOI: 10.1016/j.ssmph.2020.100697
|View full text |Cite
|
Sign up to set email alerts
|

A bio-ecological framing of evidence on the determinants of adolescent mental health - A scoping review of the international Health Behaviour in School-Aged Children (HBSC) study 1983–2020

Abstract: This paper extracts, organises and summarises findings on adolescent mental health from a major international population study of young people using a scoping review methodology and applying a bio-ecological framework. Population data has been collected from more than 1.5 million adolescents over 37 years by the Health Behaviour in School-Aged Children: WHO Cross-National (HBSC) Study. The paper reviews the contribution that this long standing study has made to our understanding of the individual, developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 136 publications
(95 reference statements)
2
77
0
4
Order By: Relevance
“…[ 31 , 32 ] The perception of a lack of reciprocal caring relationships with one's peers, which provides a feeling of belonging and support, may cause an adolescent to experience greater feelings of loneliness and to assess their social network more negatively. [ 32 , 33 ] According to researches, [ 16 , 20 , 21 ] having social friends influences students’ CB or CV. Negative support from peers has been associated with CB, according to Hellfeldt et al [ 24 ] A study suggested that students who dropped out of school were more likely to become perpetrators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31 , 32 ] The perception of a lack of reciprocal caring relationships with one's peers, which provides a feeling of belonging and support, may cause an adolescent to experience greater feelings of loneliness and to assess their social network more negatively. [ 32 , 33 ] According to researches, [ 16 , 20 , 21 ] having social friends influences students’ CB or CV. Negative support from peers has been associated with CB, according to Hellfeldt et al [ 24 ] A study suggested that students who dropped out of school were more likely to become perpetrators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in an important period in the formation of their life values and self-development, these students can access information and create interpersonal relationships using digital media, so it is very important to gain insight into the underlying causes of CB and CV, which will contribute to the prevention of CB and CV and promote health and well-being among this particular group of students. [ 16 ] However, so far, adolescents who attend vocational high school, at least in China, have remained absent in research regarding CB and CV.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of research has shown that adolescents are more likely than children and adults to engage in risky (offline) activities (Blum & Nelson-Mmari, 2004; Centers for Disease Control and Prevention, 2011; Currie et al, 2012; Quinn & Fromme, 2011; Zweig, Lindberg, & McGinley, 2001). FTT (Reyna & Brainerd, 1995, 2011) has emerged as one of the major paradigms to successfully explain adolescents’ and adults’ risk taking in domains such as health (Reyna, 2008) and sexual behavior (Mills, Reyna, & Estrada, 2008; Reyna & Adam, 2003).…”
mentioning
confidence: 99%
“…According to Bronfenbrenner's bio-ecological model, there is an interaction between the environmental, organizational, and personal levels [47]; we found this to be relevant in our study, as we focused on students in the school setting. However, this interaction did not prove to show a difference between health-promoting behaviors between HPS and non-HPS schools.…”
Section: Discussionmentioning
confidence: 89%